Strategi Komunikasi Pemasaran House Of Smith Melalui Live Streaming Tiktok dalam Meningkatkan Brand Awarenes dan Penjualan di Era New Normal - Nadia Nadia Ayu Budiani; Ferry Darmawan (UNISBA Press, 2023)
Abstract. Live streaming on social media that creates new opportunities and trends makes TikTok a place for publications containing interesting information to listen to. Based on the research objectives, it was found